Evaluasi Kepuasan Pasien Rawat Inap Dan Rawat Jalan Terhadap Pelayanan Gizi Pasien Diet Diabetes Mellitus Di RSU PKU Muhammadiyah Bantul Yogyakarta - Anggrianni, Silvia; , Dr. dr. Iwan Setiawan Adji, Sp. THT - KL; , Dr. Amin Mustofa, Sp.Ak. MARS (2017)
This research aims to identify and evaluate: 1) the performance of health workforce to satisfaction of patient with diabetes mellitus. 2) The obedience of eating schedule to satisfaction of patient with diabetes mellitus. 3) The obedience of food type to satisfaction of patient with diabetes mellitus. The data of this research is the premier data which was obtained from the answers of 100 respondents with accidental sampling method. This research is using multiple linear regression analysis. The test result concluded that all variables instrument are valid and reliable as a data collecting tool. In the data analysis shows that: 1) There is effect of the performance of health workforce to satisfaction of patient with diabetes mellitus. 2) There is not effect of the obedience of eating schedule to satisfaction of patient with diabetes mellitus. 3) There is not effect of the obedience of type food to satisfaction of patient with diabetes mellitus.